2007
DOI: 10.1074/jbc.m611664200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of a Regulatory Cascade Controlling Transcription of the Pseudomonas aeruginosa Type III Secretion System

Abstract: Pseudomonas aeruginosa is a Gram-negative opportunistic pathogen and a primary cause of pneumonia and urinary tract infections in intensive care units (1, 2). Among the most vulnerable individuals are those with immunodeficiency, cystic fibrosis, or severe burns or who require mechanical ventilation. A major virulence determinant of P. aeruginosa is a type III secretion system (T3SS). 2 The T3SS encodes a multiprotein complex, called an injectisome, which functions by injecting or translocating effector protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 24 publications
(34 reference statements)
6
53
0
Order By: Relevance
“…1). This finding is consistent with the fact that the binding affinity of ExsC is greater for ExsE than ExsD (37). Additionally, our data suggest that the affinity of ExsD is greater for ExsC than for ExsA.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…1). This finding is consistent with the fact that the binding affinity of ExsC is greater for ExsE than ExsD (37). Additionally, our data suggest that the affinity of ExsD is greater for ExsC than for ExsA.…”
Section: Discussionsupporting
confidence: 81%
“…In either case, the outcome would promote formation of the inhibitory ExsD·ExsA complex. A previous study demonstrated that addition of ExsE to the ExsD·ExsC complex results in the release of ExsD (37). We also found that incubation of ExsA His and the ExsD·ExsC His complex with ExsE His resulted in the release of free ExsD.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…It consists of different levels, transcriptional, post-transcriptional, and post-translational. The expression of effector protein is regulated by the major transcriptional activator ExsA in response to environmental signals [21]. These signals include direct contact with host cell, and low calcium.…”
Section: Regulationmentioning
confidence: 99%